Acerca del método historiográfico de Tucídides: el episodio de la peste (Historiae II.47-54) - Melone, Juan Manuel (2014)
In his account of the episode of the plague in Hist. 2, 47-54, Thucydides intertwined several discursive fields – science, drama, moral reflection – in order to historicize a phenomenon so abrupt and violent that it sank the Athenians into deep perplexity and despair. Through a rhetorical analysis of the passage, this paper proposes a reflection on Thucydides’s historiographical method.